Patient and Physician Exposure to Artificial Intelligence Hype - Monteith, Scott; Glenn, Tasha; Geddes, John R.; Whybrow, Peter C.; Achtyes, Eric D.; Bauer, Rita; Bauer, Michael (Pharmacopsychiatry, 2025)
Both patients and physicians are routinely exposed to the corporate promotion of artificial intelligence (AI) for healthcare products. Hype for AI products may impact both patient behavior and attitudes about healthcare. Corporate AI hype may intentionally overlook the known limitations associated with AI products and focus solely on potential benefits. As AI is increasingly integrated into medicine, physicians are also routinely subject to AI hype. As the promotion and use of AI products have grown dramatically in recent years, physicians should be aware of the potential benefits and risks of AI products despite the hype.
Keywords: artificial intelligence; AI hype; medical hype; hype